Psychological Consequences Among Residents and Fellows During the COVID-19 Pandemic in New York City: Implications for Targeted Interventions. (December 2021) - Kaplan, Carly A.; Chan, Chi C.; Feingold, Jordyn H.; Kaye-Kauderer, Halley; Pietrzak, Robert H.; Peccoralo, Lauren; Feder, Adriana; Southwick, Steven; Charney, Dennis; Burka, Larissa; Basist, Madeleine; Ripp, Jonathan; et al.
Abstract : Purpose: To examine the psychological impact of the COVID-19 pandemic on medical trainees (residents and fellows) working at Mount Sinai Hospital (MSH) in New York City (NYC), the initial epicenter of the United States pandemic. Method: The authors administered a survey to 991 trainees in frontline specialties working at MSH in NYC between April and May 2020. The instrument assessed symptoms of major depressive disorder, generalized anxiety disorder, COVID-19-related posttraumatic stress disorder, and burnout. Psychiatric screens were aggregated into 1 composite measure, and meeting criteria on any of the 3 scales was considered a positive screen for psychiatric symptoms. The survey also assessed COVID-19-related exposures, worries, coping strategies, and desired interventions. Multivariable logistic regressions were conducted to identify factors associated with psychiatric symptoms and burnout. Results: Of the 560 respondents (56.6% response rate), 29.7% screened positive for psychiatric symptoms and 35.8% screened positive for burnout. History of a mental illness, COVID-19-related duties and personal/career worries, and coping by substance use were associated with increased likelihood of screening positive for psychiatric symptoms. Positive emotion-focused coping and feeling valued by supervisors were associated with decreased likelihood. Internal medicine and surgical specialties, a history of mental illness, increased duty hours, duty-related worries, personal/career worries, coping via self-blame and venting, and coping via substance use were associated with higher odds of burnout. Feeling valued by supervisors was associated with decreased burnout odds. The most common crisis-related needs included access to personal protective equipment, food provisions, and financial support. Conclusions: Psychological distress and burnout affected approximately one-third of trainees sampled during the height of the pandemic in NYC. As the pandemic surged beyond NYC, these findings suggest that interventions should include addressing basic needs, promoting leadership affirmation, moderating duty hours, supporting trainees financially, and enhancing mental health support. Abstract : Supplemental Digital Content is available in the text.